The analysis of transcription factor CsHB1 effects on caffeine accumulation in tea callus through CRISPR/Cas9 mediated gene editing. - Ma, W.; Kang, X; Liu, P.; Zhang, Y.; Lin, X.; Li, B.; Chen, Z.
Caffeine is a important metabolite in tea. In previous study, transcription factor CsHB1 was cloned from tea plants via yeast one-hybrid using yhNMT1 as bait. In this study, the expression of CsHB1 and yhNMT1 in tea plants was analyzed by qRT-PCR, the effect of CsHB1 on the expression of yhNMT1 was determined by tobacco transient expression system, and the CsHB1 was assembled into pYLCRISPR/Cas9Pubi-H vector followed by transgene to tea callus. Our results showed that the expression of CsHB1 was similar to that of yhNMT1. The overexpression of CsHB1 showed no significant effect on yhNMT1 in tobacco leaves. The constructed pYLCRISPR/Cas9Pubi-H-CsHB1 vector was successfully transformed into tea callus, and CsHB1 gene was mutated directionally. In transgenic callus, the expression of CsHB1 and yhNMT1 decreased by 65 percent and 93 percent, respectively, and the accumulation of caffeine decreased by 97.5 percent, which indicated that yhNMT1 gene was regulated by CsHB1. Our results will help to understand the regulation mechanism of caffeine biosynthesis in tea.
Keywords: TEA; CAFFEINE; CSHB1 TRANSCRIPTION FACTOR; GENE EDITIN; GN-METHYLTRANSFERASE (NMT)